The Role of Islamic Education Management in Improving Human Resources: A Review of the Implementation of Islamic Education in Indonesia - Sarpendi, Sarpendi; Komalasari, Maya Ayu (CV. Creative Tugu Pena, 2023)
This research aims to provide various innovations in improving human resources in an Islamic educational institution. This research was conducted by collecting journal articles to combine ideas and innovations that a leader or management can do in an Islamic educational institution. Planning in an Islamic educational institution is important for achieving maximum results. This research aims to relieve leaders or management in Islamic educational institutions in innovating to advance their human resources to keep up with the times and fierce competition, especially in Islamic education. Besides, the purpose of this research is expected to be used as a reference in improving human resource management. This systematic review shows that the existing management in Islamic educational institutions is in dire need of various motivations and innovations in improving its human resources. a) the characteristics of Islamic education management must be based on the Qur'an and Hadith, b) the foundation of Islamic education management is based on four foundations: theoretical foundations, rational foundations, and rational foundations, c) Islamic education management is based on hablu min an-nas (human-oriented) and hablu min Allah (oriented to Allah SWT), d) the key to achieving success in an Islamic educational institution is the desire to learn in everything continually. Positively, this is to raise the spirit of its human resources. Keywords: Islamic Education Management, Human Resources, Islamic Education